2016
DOI: 10.5152/balkanmedj.2016.141033
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolic Syndrome and Affecting Factors among Individuals Aged 30 and over in Balçova District of İzmir

Abstract: Background:The studies have shown that metabolic syndrome (MetS) leads to an increase twice as much in cardiovascular diseases (CVD) and four times as much in diabetes mellitus (DM) prevalence since the second half of the 20 th century. Aims: This study aims to determine and discuss the prevalence of the MetS and co-factors among individuals at the age of 30 and over in Balcova district of İzmir province according to the American National Cholesterol Education Program -Adult Treatment Panel III (NCEP ATP III) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The prevalence rate of MetS among adults measured in the literature is heterogeneousmainly ranging from 12% to 35%. First, the estimates depend on the population studied for examples, Enkh-Oyun et al (1) estimated the prevalence of MetS at 32.8 % for a representative sample in Mongolia while the prevalence rates for Malaysia is 16.6% (2).Second, prevalence depends on the definition retained for MetS, in the Turkish adult population prevalence vary from 27.4% to 36.9 % considering the definition applied (3). There are several guidelines (Table 1): the World Health Organization (WHO 1998) (4), the National Cholesterol Education Program-Adult Treatment Panel III (NECP-ATP III 2005) (5), the American Heart Association (AHA 2005) (6), the International Diabetes Federation (IDF 2006) (18), that why an harmonized definition from IDF/AHA/National Heart Lung and Blood Institute has been performed considering ethnic group's characteristics (2009) (8).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence rate of MetS among adults measured in the literature is heterogeneousmainly ranging from 12% to 35%. First, the estimates depend on the population studied for examples, Enkh-Oyun et al (1) estimated the prevalence of MetS at 32.8 % for a representative sample in Mongolia while the prevalence rates for Malaysia is 16.6% (2).Second, prevalence depends on the definition retained for MetS, in the Turkish adult population prevalence vary from 27.4% to 36.9 % considering the definition applied (3). There are several guidelines (Table 1): the World Health Organization (WHO 1998) (4), the National Cholesterol Education Program-Adult Treatment Panel III (NECP-ATP III 2005) (5), the American Heart Association (AHA 2005) (6), the International Diabetes Federation (IDF 2006) (18), that why an harmonized definition from IDF/AHA/National Heart Lung and Blood Institute has been performed considering ethnic group's characteristics (2009) (8).…”
Section: Introductionmentioning
confidence: 99%
“…The MetS prevalence in women was found to be 41.9% in our study. Other studies conducted in our country have reported the MetS prevalence in women according to IDF diagnostic criteria to vary between 38.5% and 49.8% 7,22,29,30 .…”
Section: Discussionmentioning
confidence: 67%
“…The sample of the study was identified by using the sample size formula with an unknown population. Using a 95% confidence interval, a p-value of 0.385 22 , and the sample size formula with an unknown population, the number of women required to be included in the sample was calculated as 364, and the study was completed with 372 women who met the study inclusion criteria.…”
Section: Samplementioning
confidence: 99%